Legal Analysis of Hoax Dissemination as an Unlawful Act on Social Media - Jessy Yohanes; Velliana Tanaya; Gisella Helga Xaviera (DiH: Jurnal Ilmu Hukum, 2026)
The phenomenon of hoaxes or fake news on social media has become a serious threat in Indonesia, causing horizontal conflicts, public panic, and economic losses. Spreading hoaxes constitutes an unlawful act, both criminally and civilly. While previous studies mainly emphasized criminal aspects through the UU ITE and Kitab Undang-Undang Hukum Pidana, this research also highlights civil liability under Article 1365 of the Kitab Undang-Undang Hukum Perdata, which provides for compensation to victims. The study aims to analyze the legal-normative framework concerning the spread of hoaxes as an unlawful act and to formulate the forms of criminal and civil liability that may arise. Using a normative juridical method with a statute approach, the research examines primary legal materials, particularly UU No. 1 Tahun 2024 (Second Amendment to the UU ITE), and relevant secondary materials. The findings reveal that hoax dissemination fulfills the elements of a tort under Article 1365 of the KUHPerdata namely, an act, unlawfulness (violating rights or propriety), fault (including negligence in verification), loss (material or immaterial), and causality. The study’s novelty lies in its dual analysis combining criminal and civil perspectives. In addition to criminal sanctions imprisonment of up to six years and/or a fine of up to IDR 1 billion under Article 45A of the UU ITE, victims may also pursue civil claims for damages. This dual-path approach enriches legal scholarship and provides practical guidance for victims to achieve comprehensive justice through both criminal punishment and civil compensation.